Integrated HVSR Microtremor and Electrical Resistivity Analysis for Identifying Shallow Fluid Migration Pathways in Sangubanyu, Central Java, Indonesia - Hartono Hartono; Oscar Kaeni; Jasuri (CV FOUNDAE, 2026)
Surface manifestations of oil seepage and geothermal discharge indicate active subsurface fluid migration, but identifying shallow migration pathways in structurally complex volcanic terrains remains challenging using a single geophysical method. This study investigates shallow fluid migration in the Sangubanyi area, Central Java, Indonesia, through the integrated interpretation of Horizontal-to-Vertical Spectral Ratio (HVSR) microtremor measurements and Schlumberger resistivity sounding. HVSR-derived shear-wave velocity (Vs) models were integrated with resistivity-depth models to constrain subsurface layering and identify geophysical boundaries related to fluid migration. MSB-02 exhibits a dominant frequency of 1.32 Hz with an amplification factor of 4.32. The representative Vs model consists of a low-velocity layer of approximately 380 m/s extending to a depth of about 70 m, underlain by a higher-velocity layer of approximately 1900 m/s. Resistivity models reveal conductive zones of approximately 7–30 Ω·m contrasting with resistive volcanic units exceeding 500 Ω·m. The coincidence between the Vs impedance contrast and the resistivity anomaly is interpreted as a geophysical boundary associated with lithological variation and fault-related deformation. Integrated interpretation suggests that fault- and fracture-related permeability provides the principal vertical pathway for fluid ascent, whereas the more permeable Kaligetas Formation facilitates lateral fluid redistribution, explaining the close spatial association between hot spring manifestations and localized oil seepage. Based on the available near-surface geophysical evidence, the seepage is interpreted as a localized surface expression of structurally controlled shallow fluid migration rather than direct evidence of significant shallow hydrocarbon accumulation.